Pengaruh Tarif Impor Amerika Serikat dan China, Nilai Tukar, serta Nilai Ekspor Non-Migas terhadap Neraca Perdagangan Indonesia - Cintia Rahma; Nurbetty Herlina Sitorus; Rizka Malia (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the impact of the U.S.–China trade war on Indonesia’s trade balance through the variables of U.S. import tariffs on China, Chinese import tariffs on the United States, the rupiah exchange rate, and the value of non-oil and gas exports. This study uses time-series data from 1995 to 2024 obtained from the Central Statistics Agency (BPS), the World Integrated Trade Solution (WITS), and Bank Indonesia. The analysis method used is the Autoregressive Distributed Lag (ARDL) model to identify short-term and long-term relationships among the variables. The results indicate that, in the long term, the exchange rate and non-oil and gas exports have a significant impact on Indonesia’s trade balance, while import tariffs have a more limited and indirect effect through the trade diversion mechanism. In the short term, fluctuations in global variables have a more volatile impact on the trade balance. These findings suggest that the stability of Indonesia’s trade balance is more determined by domestic factors, such as export competitiveness, than by global tariff policies. Therefore, strategies for export diversification and strengthening the domestic industry are needed to enhance resilience against external shocks.